Regio- and stereoselective synthesis of benzothiazolo-pyrimidinones via an NHC-catalyzed Mannich/lactamization domino reaction† †Electronic supplementary information (ESI) available. CCDC 1029497. For ESI and crystallographic data in CIF or other electronic format see DOI: 10.1039/c4cc08594a - Ni, Qijian (Royal Society of Chemistry, 2015)

(untitled)
An NHC-catalyzed regio- and stereoselective Mannich/lactamization domino reaction of N-(benzothiazolyl)imines with α-chloroaldehydes has been developed.